Neighborhood Social Capital, Neighborhood Attachment, and Dental Care Use for Los Angeles Family and Neighborhood Survey Adults - Chi, Donald L. (American Public Health Association, 2013)
Objectives. We tested the hypothesis that neighborhood-level social capital and individual-level neighborhood attachment are positively associated with adult dental care use. Methods. We analyzed data from the 2000–2001 Los Angeles Family and Neighborhood Survey that were linked to US Census Bureau data from 2000 (n = 1800 adults aged 18–64 years across 65 neighborhoods). We used 2-level hierarchical logistic regression models to estimate the odds of dental use associated with each of 4 forms of social capital and neighborhood attachment. Results. After adjusting for confounders, the odds of dental use were significantly associated with only 1 form of social capital: social support (adjusted odds ratio [AOR] = 0.85; 95% confidence interval [CI] = 0.72, 0.99). Individual-level neighborhood attachment was positively associated with dental care use (AOR = 1.05; 95% CI = 1.01, 1.10). Conclusions. Contrary to our hypothesis, adults in neighborhoods with higher levels of social capital, particularly social support, were significantly less likely to use dental care. Future research should identify the oral health–related attitudes, beliefs, norms, and practices in neighborhoods and other behavioral and cultural factors that moderate and mediate the relationship between social capital and dental care use.